2001
DOI: 10.1038/sj.gt.3301538
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated transfer of the p53 family genes, p73 and p51/p63 induces cell cycle arrest and apoptosis in colorectal cancer cell lines: potential application to gene therapy of colorectal cancer

Abstract: p53 gene therapy is being tested clinically for the treatment of human cancer, however, some cancer models (in vivo and in vitro)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…Direct sequencing was carried out to verify the integrity of the inserted DNA sequences. Procedures used to generate, purify and infect replication-deficient CHFR-containing recombinant adenoviruses (Ad-CHFR) have been described earlier (Sasaki et al, 2001;Satoh et al, 2003). A recombinant adenovirus containing the enhanced green fluorescent proteins (EGFP) gene (Ad-EGFP) was generated as a control.…”
Section: Plasmids and Recombinant Adenovirusesmentioning
confidence: 99%
“…Direct sequencing was carried out to verify the integrity of the inserted DNA sequences. Procedures used to generate, purify and infect replication-deficient CHFR-containing recombinant adenoviruses (Ad-CHFR) have been described earlier (Sasaki et al, 2001;Satoh et al, 2003). A recombinant adenovirus containing the enhanced green fluorescent proteins (EGFP) gene (Ad-EGFP) was generated as a control.…”
Section: Plasmids and Recombinant Adenovirusesmentioning
confidence: 99%
“…20 Another independent study demonstrated the potential therapeutic use of p73 expressing adenovirus against colorectal cancer cells. 21 In the present study, we investigated the cytotoxic potential of a replicationdeficient recombinant adenovirus expressing p73b (Adp73) against a panel of human cancer cell lines of diverse tissue origin. We analyzed the infectivity of Ad-p73 by monitoring the cellular p73 and p21 WAF1/CIP1 levels as well as the cytotoxicity against a variety of cancer cells.…”
mentioning
confidence: 99%
“…[31][32][33] In colon cancer cell lines, TAp63g and TAp73b have the strongest pro-apoptotic potential of all of the p63 and p73 isoforms. 34 We introduced p53, TAp63g and TAp73b into 56 cancer cell lines using an adenoviral vector (Ad) and compared their effects on cell death and apoptosis by using flow cytometry. The sub-G1 fraction (%) contains apoptotic cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that p53 family activity correlates with tumor cell sensitivity to certain DNA-damaging agents. 34,[36][37][38][39] In general, gene therapy is given in combination with chemotherapy; p63-53O may have potential as a cancer gene therapy agent either alone or in combination with chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%